Analyzing the Application of Different Sources of Recycled Concrete Aggregate for Road Construction. Issue 8 (August 2020) - Ardalan, Nazanin; Wilson, Douglas J.; Larkin, Tam J.
Because of the environmental, planning, and resource restrictions in the exploration and processing of natural aggregates, interest in better utilizing recycled aggregates in road pavement construction is increasing. Several researchers have investigated the characteristics of recycled concrete aggregate (RCAg) with the aim of understanding its performance as a base-course unbound material. As the pavement design techniques and the properties of re-processed RCAg in each country are non-homogeneous, previous international research on recycled aggregate cannot necessarily be incorporated in New Zealand's pavement specifications. Moreover, RCAg is mainly sourced from vertical or horizontal concrete demolished structures. These sources of material have different engineering characteristics, and there is a lack of information about their performance. This paper investigates the difference between the properties of these two vertical and horizontal sources, and it evaluates their application as an unbound granular base-course material as opposed to an alternative layer in the pavement, for road construction in New Zealand. The physical properties of RCAgs engineering performance (durability) were evaluated through experimental laboratory-based tests. Also, the characteristics of the tested RCAgs were compared with the specification of base-course materials (NZ Transport Agency M4) in New Zealand, and their appropriateness for high-performing pavement construction layers was assessed. According to the tests results, the tested RCAgs have proven to meet the "premium" base-course grade product, and it is expected that recycled crushed concrete, if production processes are appropriately managed, could have great potential use as a base-course material in road construction and in some cases perform better than common natural aggregates.